Effects of salient factors on the pursuit of higher education among multicultural youth in Hong Kong - Yuen, Celeste Y. M.; Cheung, Alan C. K.; Leung, K. H. (Frontiers in Psychology, 2023)
This study presents novel and compelling evidence of the disparities in factors influencing the beliefs and aspirations for higher education among mainstream and immigrant youth in Hong Kong, particularly those who are underprivileged. We developed and validated a psychometric questionnaire, known as the Post-Secondary Education Pursuit Instrument (PSEPi), which was administered to 4,850 students aged between 15 and 18 years old from 23 secondary schools. The objective of this study was to explore the factors that impact students’ choices and plans for higher education. The results of the one-way Multivariate Analysis of Variance (MANOVA) analysis deepen our understanding of the differential effects of success and obstacle factors on students’ higher education pursuits across various cultural groups. The underprivileged mainstream, Chinese immigrant, and ethnic minority South Asian youth reported a perceived glass ceiling effect associated with their ethnic backgrounds, as well as financial aid barriers, while pursuing higher education, in contrast to their average Hong Kong mainstream counterparts (mean Cohen’s d = 0.40). The direct effects and multiple mediation analyses demonstrated that significant others’ influence, particularly the influence of parents, and locus of control are prime determinants of the perceived usefulness of higher education for all student groups. The implications are that educational policies should be implemented to level the playing field in higher education admissions for both privileged and underprivileged youth in Hong Kong and other international countries. Overall, this study provides robust empirical evidence that can be utilized to enhance educational policies and practices to bridge the gap between mainstream and underprivileged immigrant youth in their pursuit of higher education.